DEVELOPING ENGLISH READING MATERIALS BASED ONCONTEXTUAL TAECHING AND LEARNINGFOR GRADE X STUDENTS OF AUDIO VIDEO PROGRAM AT SMK N 1 PERCUT SEI TUAN - Hera Parisa; Indra Hartoyo; Rika Rika (Universitas Negeri Medan, 2018)
This study aims to develop English reading materials needed by students of Vocational School and develop English reading materials for students of Audio Video Program based on Contextual Teaching and Learning. The research was conducted by Research and Development (R & D) design through six phases; gathering information and data, analyzing data, designing new materials, validating by experts, revising, and final product. It was conducted in SMK N 1 PercutSei Tuan, especially grade X. The data were gathered by administering interview and distributing questionnaire to 23 respondents to get the students’ needs. The interview and questionnaire results prove that the students need English reading materials which contain English for Audio Video program.The average scores are the first from English lecturer and the second from English teacher. It means that the developing materials categorized as suitable or approriate for grade X of Audio Video program. Key words: Research and Development (R & D), reading materials, Audio Video Program.